PROFESSIONAL COMPETENCY DEVELOPMENT OF SECONDARY SCHOOL PRINCIPAL BY ONLINE IN THE CITY OF BANJARBARU - Zaenal Fanani (European Journal of Humanities and Educational Advancements, 2022)
This scientific paper is motivated by the low competence of graduate students and the not yet optimal development of the professional competence of school principals. This is because the guidance for improving the professional competence of school principals has not been oriented to graduate competency standards as a national education goal. The formulation of the problem studied is How is the professional competence of junior high school principals in the city of Banjarbaru? What are the obstacles for junior high school principals in developing professional competence in the city of Banjarbaru? How is the professional competence development of junior high school principals online in the city of Banjarbaru? The purpose of this paper is to find out the competencies and obstacles to developing the professional competence of junior high school principals in the city of Banjarbaru and the design of the professional competence development of junior high school principals online in the city of Banjarbaru. The research method used is qualitative with a research focus on the design of professional competency development for junior high school principals in the city of Banjarbaru. The technique of collecting data is through interviews. Data analysis techniques to find relevant information, using interactive analysis model by Miles and Huberman (1994) and comparative model by Bogdan & Biklen (2003). The results showed that the professional competence of the junior high school principal of Banjarbaru city was not in accordance with the national education standard. The obstacles to developing the professional competence of junior high school principals in the city of Banjarbaru include lack of funds and facilities, unequal understanding between school principals and the education office, lack of assistance from supervisors, lack of relevance of technical guidance materials to professional needs and lack of understanding of school principals about national standards. education and national curriculum. The design for developing the professional competence of junior high school principals online in the city of Banjaru includes the coherence of training materials and is oriented to graduate competence as well as training patterns with the integration of independent learning, on the job learning and in service training carried out in two stages and online. Suggestions for BPSDMD South Kalimantan Province to apply the design of principal competency development in the training system. Suggestions for the Banjarbaru City Education Office to build a common vision to provide services for students to achieve graduate competency standards. Suggestions for the Superintendent of Supervision to focus on fostering the professional development of school principals so that they are oriented to the competency standards of student graduates